The terminologies associated with development and marginalisation for Orang Asli in Malaysia. Issue 7 (2nd October 2016) - Amir Zal, W.A.; Omar, Mustaffa; Salleh, Hood
ABSTRACT: Previously, any failure of Orang Asli development activity in Malaysia, was characterised by using a single term in all situations − "marginalisation". This generalisation was unfair to everyone involved in the Orang Asli development process, made it difficult to resolve problems, and resulted in tendencies to blame certain people. Based on ethnographic research in Kuala Gandah, Pahang, Malaysia, this article allocates three terms in the Orang Asli development marginalisation discourse: "secluded", "isolated", and "marginalised". "Secluded" refers to development activity that accidentally marginalises. "Isolated" refers to development activity that directly and deliberately marginalises. "Marginalised" refers to the Che Wong that were eliminating or avoiding development. These terms were exposed by weaknesses in the implementation of development, namely the role of a single dominant approach in development activities – the top-down approach – and a tendency to generalise the marginalisation of the Orang Asli. This article recommends that more care be taken to apply a development approach that deals with situations on a case-by-case basis and that utilises the partnership approach to development, involving all parties in all phases.